Thermal Reverse-Engineered Synthesis and Catalytic Activity of Nanogold-Containing Silica Aerogels - Hanna Judit Csupász-Szabó; Boglárka Döncző; Máté Szarka; Lajos Daróczi; István Lázár (Gels, 2025)
Silica aerogels are extensively used as catalyst supports due to their mesoporous structure and chemical inertness. In this study, SiO2–AuNP aerogels containing gold nanoparticles (AuNPs) were synthesized using the sol-gel method followed by supercritical CO2 drying. The inclusion of polyvinyl pyrrolidone (PVP) as a stabilizing agent preserved the gold particle sizes during the gelation process. In contrast, aerogels synthesized without PVP contained enlarged AuNP aggregates, resulting in a shift in the plasmon resonance color from red to bluish or blue–grey. Thermal treatment of these bluish-colored aerogels at high temperatures restored their red coloration, visually indicating the breakdown of large gold clusters into individual nanoparticles. Both types of aerogels were characterized using SEM, TEM, 3D optical microscopy, UV–vis and ATR-IR spectroscopy, and N2 porosimetry, with their properties analyzed as a function of annealing temperature. Their catalytic activity was evaluated through the reduction of 4-nitrophenol with sodium borohydride, and both aerogel types demonstrated catalytic activity. This thermal conversion of large clusters into individual nanoparticles within an aerogel matrix introduces a new and promising approach for creating catalytically active nanogold-containing aerogel catalysts.